2005
DOI: 10.1007/s11011-005-7911-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ammonia-Induced Astrocyte Swelling

Abstract: Astrocyte swelling represents the major factor responsible for the brain edema associated with fulminant hepatic failure (FHF). The edema may be of such magnitude as to increase intracranial pressure leading to brain herniation and death. Of the various agents implicated in the generation of astrocyte swelling, ammonia has had the greatest amount of experimental support. This article reviews mechanisms of ammonia neurotoxicity that contribute to astrocyte swelling. These include oxidative stress and the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
130
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 159 publications
1
130
0
1
Order By: Relevance
“…A high-protein diet would cause hyperammonemia, and ammonia has been reported to cause deterioration of mitochondria through the production of reactive oxygen species (1,29), and it has been known to provoke central and peripheral fatigue (14) and would alter energy consumption. Fumarate, which is a degradation product of protein and amino acids, has been reported to cause impairment of muscle contractility (21) and fatigue (20).…”
Section: Discussionmentioning
confidence: 99%
“…A high-protein diet would cause hyperammonemia, and ammonia has been reported to cause deterioration of mitochondria through the production of reactive oxygen species (1,29), and it has been known to provoke central and peripheral fatigue (14) and would alter energy consumption. Fumarate, which is a degradation product of protein and amino acids, has been reported to cause impairment of muscle contractility (21) and fatigue (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aquaporin (AQP) 4, the most abundant water channel in the CNS is present on the astrocytes (Vizuete et al, 1999;Rao et al, 2003) and plays a crucial role in brain edema formation observed after CNS insults or in disease (Manley et al, 2004;Badaut et al, 2002;Alexander et al, 2003). Edema could lead to increased intracranial pressure, resulting in brain herniation and finally death (Norenberg et al, 2005).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Furthermore, aquaporin (AQP) 4, the most abundant water channel in the CNS is present on the astrocytes (Vizuete et al, 1999;Rao et al, 2003) and plays a crucial role in brain edema formation observed after CNS insults or in disease (Manley et al, 2004;Badaut et al, 2002;Alexander et al, 2003). Edema could lead to increased intracranial pressure, resulting in brain herniation and finally death (Norenberg et al, 2005).Septic encephalopathy although common and devastating, the role of the different mechanisms behind this occurrence, still remains unclear. Although cytokines such as TNF-α are key mediators of sepsis (Lucas et al, 1997), knowledge as to their effects in brain is still being investigated, in the setting of endotoxemia.…”
mentioning
confidence: 99%
“…This is accomplished in the astrocyte via glutamine synthetase (GS). Glutamine is osmotically active and can cause astrocytic swelling leading to cytotoxic oedema (Batshaw et al 1986;Bender and Norenberg 1996;Norenberg 1996;Norenberg et al 2005). Studies in which the GS inhibitor methionine sulfoximine is administered demonstrate reduced ammonia-induced brain oedema in both in vivo (Takahashi et al 1991) and in vitro models (Blei et al 1994;Norenberg and Bender 1994;Takahashi et al 1991).…”
Section: Pathogenic Mechanisms Of Acute Hyperammonaemiamentioning
confidence: 99%